Analisis Berpikir Kritis Siswa SMAN 4 Padang pada Materi Pencemaran Lingkungan - Rosyidah Syahrul; Ramadhan Sumarmin; Helendra Helendra; Relsas Yogica (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2021)
The individual's capacity to be effective in life is determined by his reasoning abilities, especially with the ultimate goal of overcoming life's problems. Basic reasoning is a clear and coordinated cycle of reasoning used in critical, dynamic thinking, investigating and leading logical examinations. This research aims to determine the critical thinking abilities of students at SMAN 4 Padang on Environmental Pollution Material. This type of research is descriptive, the sample is determined by proportional random sampling. The sample size was 125 students from 50% of each class member who were taken randomly. Students' critical thinking tests are analyzed per indicator consisting of: Analysis, Evaluation, Deductive and Inductive. Based on the results of the critical thinking analysis of students at SMAN 4 Padang, the average percentage was 71.99% in the high category. Almost any part of the upper level character can be balanced in the student, so that one can make tentative decisions.